Immune gene network of neurological diseases: Multiple sclerosis (MS), Alzheimer's disease (AD), Parkinson's disease (PD) and Huntington's disease (HD). Issue 12 (December 2021) - Mukherjee, Shradha
Abstract: Neurological diseases, such as MS, AD, PD and HD, are a major health concern of the elderly population, but still therapeutic options are limited. Recent advances in genomic sequencing and bioinformatics, present an opportunity to understand mechanisms of these diseases for identification of therapeutic targets. Several studies have shown association of immune dysfunction with immune system mediated neurological disease, MS, as well as neurodegenerative diseases (AD, PD and HD). However, similarities and differences in role of the immune system, immune pathways and immune cell types in these diseases remains unknown. In this study, immune cell type signature genes in gene networks associated with neurological diseases, MS, AD, PD and HD was investigated using meta-analysis and bioinformatics methods. Application of Weighted Gene Co-expression Network Analysis (WGCNA) on publicly available gene expression datasets (microarray and RNA-seq) revealed a ModArray_04 module (microarray) or ModRNAseq_06 module (RNA-seq), significantly associated with MS, AD, PD and HD. Hypergeometric enrichment test revealed significant enrichment of immune cell type genes in these neurological disease modules. This study demonstrates that immune system mediated neurological disease, MS and neurodegenerative diseases (AD, PD and HD), share a common gene network characterized by immune cell type signature genes (microglia, monocytes and macrophages) and are probable targets for therapeutic intervention. In summary, this work shows a connection between MS, a disease where the role of the immune system and inflammation is established, and neurodegenerative diseases (AD, PD and HD) where the role of inflammation is still a hypothesis. Abstract : Neurodegenerative diseases, Brain diseases, Bioinformatics, Gene networks, WGCNA, Gene expression, Biomarker, Immune system, Microglia, RNA-seq.